Taschenrechner im Mathematikunterricht der Grundschule (mathematica didactica, 2006)
Calculators in primary schools? We report on experiences and results from a research project in 8 schools with 186 pupils. We analyze if the use of simple calculators enhances multiplicative computation skills and number sense of 3rd graders (age about 9years).